Distinguishing Old From New Referents During Discourse Comprehension: Evidence From ERPs and Oscillations - Nieuwland, Mante S.; Coopmans, Cas W.; Sommers, Rowan P. (Frontiers in Human Neuroscience, 2019)
In this EEG study, we used pre-registered and exploratory ERP and time-frequency analyses to investigate the resolution of anaphoric and non-anaphoric noun phrases during discourse comprehension. Participants listened to story contexts that described two antecedents, and subsequently read a target sentence with a critical noun phrase that lexically matched one antecedent (‘old’), matched two antecedents (‘ambiguous’), partially matched one antecedent in terms of semantic features (‘partial-match’), or introduced another referent (non-anaphoric, ‘new’). After each target sentence, participants judged whether the noun referred back to an antecedent (i.e., an ‘old/new’ judgment), which was easiest for ambiguous nouns and hardest for partially matching nouns. The noun-elicited N400 ERP component demonstrated initial sensitivity to repetition and semantic overlap, corresponding to repetition and semantic priming effects, respectively. New and partially matching nouns both elicited a subsequent frontal positivity, which suggested that partially matching anaphors may have been processed as new nouns temporarily. ERPs in an even later time window and ERPs time-locked to sentence-final words suggested that new and partially matching nouns had different effects on comprehension, with partially matching nouns incurring additional processing costs up to the end of the sentence. In contrast to the ERP results, the time-frequency results primarily demonstrated sensitivity to noun repetition, and did not differentiate partially matching anaphors from new nouns. In sum, our results show the ERP and time-frequency effects of referent repetition during discourse comprehension, and demonstrate the potentially demanding nature of establishing the anaphoric meaning of a novel noun.